PENERAPAN MEDIA POSTER TERHADAP HASIL BELAJAR SEJARAH KEMERDEKAAN PADA SISWA TUNAGRAHITA Â - Onfiati, Sri (Pendidikan Luar Biasa, 2012)
Abstract; This study aims to examine the influence of media on the subject History of Independence poster against cognitive skills (understanding of the material) of children in special impaired and mentally retarded schools C YPPLB Ngawi. The study design used was "The One Group Pre-test Post-test Design" with before the experiment approach, namely the study used one group without a comparison group of population, in this study were students in class X impaired and mentally retarded SLB C YPPLB Ngawi which consists of 4 students aged 15-25 years. The method used in this study is the documentation and tests. Intervention materials are given in six sessions, where each end of the meeting of intervention, children are invited to conclude their discussions poster with mild and frequently asked questions about the intervention materials. Analysis of the data used is a non-parametric statistics (Sign Test). From the results obtained the conclusion that the media posters on Independence History lessons have an influence on cognitive abilities (understanding of the material) of children in special impaired and mentally retarded schools C YPPLB Ngawi.